Migrants' Remittances from Italy : International Remittances and Access to Financial Services for migrants in Turin, Italy - World Bank (Washington, DC, 2015)
This report starts by presenting the international and Italian context of international remittance flows in the past decade, as a general framework of the study (chapter two). The connection between the labor market integration of migrants with the more general economic trends in their destination countries is a crucial issue in the current academic and political debate. Trends and impacts of the economic crisis reflect themselves in micro-behaviors and affect also the transnational activities of migrants. Chapter three presents the objectives of the research and the related survey design and sampling techniques for the fieldwork, while a specific methodological note is added at the end of the report on the fieldwork phase. Chapter four focuses on empirical findings from the analysis of the 480 interviews collected. After a brief description of demographic and economic conditions of interviewed migrants, the core of this section is devoted to the analysis of migrants’ attitudes and behaviors in sending remittances, in engaging in investments and savings, and to explore changes across time and according to their occupational status at destination. In light of the global commitment to the reduction of remittance costs as a part of a more comprehensive strategy to foster the migration and development nexus, a specific section deals with remittance service providers and remittance costs revealing still room for improvement for the development of a competitive and transparent remittance market. The conclusive chapter highlights the main empirical findings and suggests further lines of analysis on migratory models, migrant economic integration and transnationalism from the collected empirical evidence.